Institutional factors influencing institutionalised supplier development initiatives in the construction industry in Zambia - Shem Sikombe; Maxwell A. Phiri (Cogent Business & Management, 2021)
The study seeks to examine the institutional factors influencing institutionalised supplier development initiatives in the construction industry in Zambia. A qualitative strategy was used to capture expert perspectives using a semi-structured interview protocol. The implementation of the initiatives is strongly affected by political influence. The findings also show that corruption has contributed to unfair competition between local and foreign contractors. Furthermore, the criterion for engaging local contractors in the initiatives is not clear. Other factors include inadequate monitoring and evaluation systems due to the lack of a robust regulatory system. However, the findings reveal that information dissemination has been very effective. There is a consensus that the initiatives have relatively contributed to the empowerment objective and knowledge transfer. The study recommends enacting binding legislation on specific projects financed entirely by the government and local contractors as award criteria to encourage main contractors to ensure an ideal subcontracting environment for contractors. The study also proposes procuring entity ratings based on the successful application of the reservation and preferential schemes. Furthermore, contractors should take preliminary qualification examinations to determine their capacity before bidding for contracts under the initiatives.
Keywords: 650; institutional factors; institutionalised supplier development; small and medium-sized contractors; construction industry; Zambia